Overview of Sleep Quality on The Incidence of Hypertension Study: Sys-tematic Literature Review - Liza Virgianti; Nurjazuli Nurjazuli; Bagoes Widjanarko (Green Publisher Indonesia, 2025)
This study investigates the impact of poor sleep quality on the incidence and severity of hypertension, drawing from a systematic review of scientific articles published between 2019 and 2024. The review synthesizes findings from various studies sourced from PubMed and Google Scholar using the keywords